Pengaruh Job Meaningfulness Terhadap Work Engagement Melalui Psychological Capital (Studi: Puskesmas Mokoau) Kota Kendari Sulawesi Tenggara, Indonesia - Rahman (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The work of health workers is a key factor in ensuring the quality and sustainability of primary health services. However, high work demands and limited resources have the potential to weaken work involvement if they are not balanced with a perception of work meaning and adequate psychological capacity. This study aims to analyze the effect of job meaningfulness on work engagement of health workers through psychological capital as a mediating variable at the Mokoau Health Center, Kendari City, Southeast Sulawesi. This study used a quantitative approach with a cross-sectional design. All health workers at the Mokoau Health Center as many as 70 people were used as research samples using the total sampling method. Data was collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS version 4.0. The results of the analysis showed that job meaningfulness had a positive and significant effect on psychological capital (β = 0.698; p < 0.05). Psychological capital was also shown to have a positive and significant effect on work engagement (β = 0.691; p < 0.05). Furthermore, job meaningfulness had a significant indirect effect on work engagement through psychological capital (β = 0.482; p < 0.05), which shows the mediating role of psychological capital in the relationship. Job meaningfulness not only contributes directly to strengthening psychological capital, but also indirectly increases work engagement of health workers. Psychological capital plays a role as the main psychological mechanism that translates the meaning of work into higher work attachment. These findings affirm the importance of a human resource management strategy that focuses on strengthening the meaning of work and psychological capital to increase the work involvement of health workers in primary health care facilities.